Manifestações do catolicismo popular no contexto urbano: Folia de Reis como resistência cultural em Sorocaba-SP (1990-2025) - Rocha, Isabela Martins de Souza (Universidade Federal de São Carlos, 2025)
This is a study on the history and survival of the only Folia de Reis group in Sorocaba, São Paulo. The “Companhia de Santos Reis da Vila Formosa” has been carrying out its journeys—bringing culture and faith to the homes of Sorocaba residents—since 1990. Based on qualitative research, with participant observation supplemented by field notebook annotations and oral history interviews with members of the Sorocaba Folia de Reis, this study explores the processes of preserving the very condition of being human within the context of popular culture and the historical formation of migrant communities. It also offers insights into how society and political powers receive and revisit their own cultural foundations, both within this small community and in other rural-based religious traditions. The study concludes that, just as the Festa de Santos Reis is diverse, the notions of territoriality and belonging are essential to understanding the experiences observed. The oral accounts collected cease to exist solely as speech and become both tangible and intangible heritage, revealing elements of a tradition rooted not only in rural imagination, but also coexisting and resisting the rapid erasure of popular cultures within urban centers.
Manifestations of Popular Catholicism in the Urban Context: Folia de Reis as Cultural Resistance in Sorocaba-SP (1990–2025)
Keywords: Folia de Reis; Tradições populares; Urbanização; Modernidade; Sorocaba; popular traditions; urbanization; modernity; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO